The push for the international regulation of cross-border access to electronic evidence and human rights - Gascón Marcén, Ana (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
This paper describes the different solutions used by China, the United States and the European Union to access electronic evidence for criminal investigations and the problems raised by their different approaches. The unstoppable trend to create mechanisms that allow authorities from one State to request data directly from a service provider located in another State is assessed together with the human rights challenges it poses and the need for the inclusion of certain safeguards in this kind of initiatives. The Second Protocol to the Budapest Convention is also analyzed as a recently negotiated multilateral solution to tackle this issue.